PERSPEKTIF KEBIJAKAN PENDIDIKAN SISTEM ZONASI DI SEKOLAH MENENGAH ATAS (SMA) KOTA DEPOK - Putra, Ibnu Aidil (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
The purpose of this study is to determine the perspectives of the school's external (community/parents) and internal (schools) regarding the zoning system policies that have occurred and the effects that has been felt positively and negatively. Based on these objectives, this research is a qualitative one using a perspective approach. With the perspective approach can describe the results of data collection through observation, interviews and documentation. Based on research that has been done this zoning system policy will eliminate the nickname of favorite schools, leveling schools in every village in Depok, saving transportation costs because of the distance from schools that relatively close, completing existing facilities in every public school in Depok in order to improve quality service in each of these schools. Suggestions in this thesis are (1) if the regional or central government creates two schools with a large population in an area, (2) holds one or two special learning classes for children who have overrated academic abilities. (3) improving the teaching human resources and infrastructures for newly built or held public schools; (4) local governments must work together to encourage students when new they are recruited for housing.